2017
DOI: 10.1097/ccm.0000000000002496
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Picture of Severe Systemic Capillary-Leak Syndrome Episodes Requiring ICU Admission

Abstract: We described the largest cohort of severe systemic capillary-leak syndrome flares requiring ICU admission. High-volume fluid therapy was independently associated with poorer outcomes. IV immunoglobulin use was not associated with improved survival; hence, their use should be considered prudently and needs further evaluation in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 27 publications
0
55
0
2
Order By: Relevance
“…There may be a benefit of immunomodulatory therapy in patients with MIS-C, severe disease, and evidence of cytokine storm syndrome and/or those with cardiac involvement. Due to recent emergence of MIS-C, no randomized trials or comparative effectiveness studies have evaluated treatment strategies, but the benefits of immunomodulatory therapy are well established in KD [ 39 ], and they are often used for the treatment of infective myocarditis [ 46 48 ] and other systemic inflammatory diseases [ 49 , 50 ]. Therefore, based on the experience in similar conditions, it appears reasonable to suggest an immunomodulation approach based on intravenous immunoglobulins (IVIGs).…”
Section: Managementmentioning
confidence: 99%
“…There may be a benefit of immunomodulatory therapy in patients with MIS-C, severe disease, and evidence of cytokine storm syndrome and/or those with cardiac involvement. Due to recent emergence of MIS-C, no randomized trials or comparative effectiveness studies have evaluated treatment strategies, but the benefits of immunomodulatory therapy are well established in KD [ 39 ], and they are often used for the treatment of infective myocarditis [ 46 48 ] and other systemic inflammatory diseases [ 49 , 50 ]. Therefore, based on the experience in similar conditions, it appears reasonable to suggest an immunomodulation approach based on intravenous immunoglobulins (IVIGs).…”
Section: Managementmentioning
confidence: 99%
“…A recent multicentre study of patients with SCLS admitted to the ICU demonstrated that therapy of acute flares with high-volume intravenous fluids was independently associated with poorer outcomes 5. Although a beneficial effect of IVIG (1–2 g/kg) during acute leaks has been suggested based on the study of a few patients,13 overall, its efficacy in the acute setting has not been established 5. In contrast, prophylactic administration of IVIG on a monthly basis clearly reduces the severity and frequency of episodes in most patients 4 14.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible triggers of CLS include idiopathic, infection, ischemia-reperfusion injury, and metformin. Idiopathic CLS, as known as Clarkson syndrome, [ 6 , 16 ] is a rare syndrome with less than 500 cases being reported so far. The typical presentation of Clarkson syndrome is recurrent episodes of increased capillary permeability with viral-like prodrome in the context of monoclonal gammopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Acute limb compartment syndrome is a good example that is accompanied by CLS and is a surgical emergency. [ 5 , 6 ] Moreover, acute compartment syndrome accompanied by CLS shows atypical presentation, which make diagnosis challenging. Here, we report a case of severe CLS following a metformin and dipeptidyl peptidase-4 (DPP-4) inhibitors overdose, which resulted in multiple limb compartment syndrome.…”
Section: Introductionmentioning
confidence: 99%